Saints for all occasions [compact disc, unabridged] - Sullivan, J. Courtney (Random House Audio, 2017)
After moving to America, a shy and responsible older sister and a gregarious young sister who thrives in their new Boston home endure the long-term repercussions of a fateful decision when the younger sister becomes pregnant.